Detection of Antibodies against Orientia tsutsugamushi Sca Proteins in Scrub Typhus Patients and Genetic Variation of sca Genes of Different Strains - Ha, Na-Young (American Society for Microbiology, 2012)
Scrub typhus, caused by Orientia tsutsugamushi infection, is one of the main causes of acute febrile illness in the Asian-Pacific region. Although early diagnosis and immediate antibiotic treatment are critical for reducing disease severity and mortality, current diagnostic methods using serological and molecular approaches have some limitations in sensitivity and applicability in clinical laboratories. In this study, we identified and characterized O. tsutsugamushi surface cell antigen (sca) family genes encoding autotransporter proteins in order to test them as novel diagnostic targets. We evaluated antibody responses against the Sca proteins in scrub typhus patient sera and examined the genetic diversity of these genes in different strains after PCR amplification. Specific antibody responses against ScaA and ScaC were observed in patients with high indirect immunofluorescence assay titers (≥1:640), whereas specific responses against ScaB and ScaE were relatively low. Genetic analysis using genomic DNAs revealed the sca genes to be quite variable among the different strains. In contrast to scaA, scaC, and scaD, which were detected in all of the tested strains, scaB and scaE were amplified differentially from the different strains, suggesting a differential presence of the genes in the genomes. Among the members of the gene family, the sequence of scaC is the most highly conserved between the different strains, and the size of scaD is the most variable due to the presence of different numbers of internal repeat sequences. These results suggest that the sca genes of O. tsutsugamushi may be valuable targets for use in combination with classical assay methods for scrub typhus diagnosis.